Mengkaji Karya Lukisan Jepang “The Great Wave Off Kanagawa” Menggunakan Kajian Teori Clive Bell - Nuraini, Rosida; Dawami, Angga Kusuma (Magenta | Official Journal STMK Trisakti, 2025)
Ukiyo-e literally means "modern painting" or paintings with themes of everyday life. One painter who is very famous for his artistic works of natural landscapes is Katsushika Hokusai. When he was old enough, Hokusai spent it creating a collection of paintings known as Thirty-Six Views of Mount Fuji (Fugaku sanjûrokkei) or thirty-six views of Mount Fuji. One of his works in the series, entitled Kanagawa-oki Nami Ura or as it is also known as "The Great Wave Off Kanagawa", is very global because the artist succeeded in making his work unique, where he represents the view of large waves accompanied by Mount Fuji using a combination of colors and techniques. unique. Significant Form, according to Clive Bell, is a relationship and combination of lines or colors that aesthetically creates a form. In his book, Clive Bell emphasizes that the quality that makes a work of art exist and without which it does not exist is called significant form. The Great Wave Off Kanagawa includes the theory put forward by Clive Bell, which is that from lines, choosing colors that are aesthetically pleasing can create aesthetic shapes.